Climate+ decision logic and SMS contents - Castillo, Rowena (2024)
The documentation focuses on Climate+ decision logic framework for sending weather-adjusted SMS alerts to rice farmers when is this identified potential climate risks based on triggers. Utilizing the RCMAS data and the seasonal and 10-day weather forecast, the framework aims to enhance crop management by providing timely advisories during critical growth stages, such as planting, fertilization, irrigation, and harvesting. Climate+ aims to mitigate climate-related risks, optimize resource use, and ultimately improve rice production sustainability.